Efektivitas Pemeriksaan Pajak Dalam Upaya Meningkatkan Penerimaan Pajak KPP Pratama Kendari Tahun 2022 - Juniarti, Eni; Irawan, Bambang; Pandoyo, Pandoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to analyze and evaluate the effectiveness of tax audits at the Kendari Pratama Tax Service Office in 2022. The theory used in this research refers to the opinion of Musaroh (2010).The research method used is descriptive qualitative by interviews, observation and documentation, measure the level of effectiveness, and then analyze the obstacles and efforts to resolve the problem. The results obtained during the research show that the tax audit at KPP Pratama Kendari 2022 is very effective with an effectiveness ratio of 104.37%. Then, the obstacles faced by tax auditors and taxpayers include limited knowledge of taxpayers regarding applicable regulations/regulations, limited taxpayer profiles, availability of audit data and raw materials, as well as the condition of the audit object. In order to minimize the various obstacles faced, these include providing outreach and education regarding tax rights and obligations to taxpayers; increasing the capacity of tax auditors; provide quality and accountable data; and increase taxpayer awareness of their tax obligations.